Meeting the Inclusion Challenge in Innovation (De Gruyter, 2025)
Users play an important role in innovation, both as a source of new ideas and insights and as accelerators of downstream adoption and diffusion. Their potential contribution is well known, but we understand less about how to realize this potential. This book addresses the question of how to release the power of users – how to help them articulate their insights and how to work with them to co-create better solutions.